The volume and monetary value of human milk produced by the world's breastfeeding mothers: Results from a new tool - Smith, Julie P.; Iellamo, Alessandro; Nguyen, Tuan T.; Mathisen, Roger (Frontiers in Public Health, 2023)
The Mothers' Milk Tool was developed to make more visible the economic value contributed to society by women's unpaid care work through breastfeeding infants and young children. This manuscript describes the development and display key features of the tool, and reports results for selected countries. For the development, we used five steps: 1) defining the tool by reviewing existing tools and scholarly literature to identify uses, approaches, design features, and required data characteristics for a suitable product; 2) specifying the best open-access data available for measurement and easy updating; 3) analyzing development options; 4) testing predictive models to fill identified breastfeeding data gaps; and 5) validating the tool with prospective users and against previous research. We developed an Excel-based tool that allows working offline, displaying preloaded data, imputing data, and inputting users’ data. It calculates annual quantities of milk produced by breastfeeding women for children aged 0-35.9 months, and the quantities lost compared to a defined biologically feasible level. It supports calculations for an individual mother, for countries, and global level. Breastfeeding women globally produce around 35.6 billion liters of milk annually, but 38.2% is currently ‘lost’ due to cultural barriers and structural impediments to breastfeeding. The tool can also attribute a monetary value to the production. In conclusion, the Mothers’ Milk Tool shows what is at risk economically if women’s important capacity for breastfeeding is not protected, promoted, and supported by effective national policies, programs, and investments. The tool is of value to food and health policymakers, public officials, advocates, researchers, national accountants and statisticians, and individual mother/baby dyads, and will assist consideration of breastfeeding in food balance sheets and economic production statistics. The tool supports the 2015 Call to Action by the Global Breastfeeding Collective by facilitating the tracking of progress on breastfeeding targets.